DEVELOPMENT OF THE AVATION SAFETY INFORMATION MONITORING SYSTEM - A. K. Blagorazumov; G. E. Glukhov; I. G. Kirpichev (Научный вестник МГТУ ГА)
This article describes the Aviation Safety Information Monitoring System, namely the architecture, algorithm of collecting and processing of the information as well as user interfaces. With the proposed model one can estimate the efficiency of the operation of aviation security in case of unlawful interference in air transport.